2021
DOI: 10.1038/s41598-021-83418-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of primary cilia promotes mitochondria-dependent apoptosis in thyroid cancer

Abstract: The primary cilium is well-preserved in human differentiated thyroid cancers such as papillary and follicular carcinoma. Specific thyroid cancers such as Hürthle cell carcinoma, oncocytic variant of papillary thyroid carcinoma (PTC), and PTC with Hashimoto’s thyroiditis show reduced biogenesis of primary cilia; these cancers are often associated the abnormalities in mitochondrial function. Here, we examined the association between primary cilia and the mitochondria-dependent apoptosis pathway. Tg-Cre;Ift88flox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…It is somewhat astonishing that especially KTC-1 cells, which are representatives of human thyroid carcinoma cells, exhibit cilia and maintain mTaar1-eGFP expression at them because in mice, papillary and follicular carcinoma are both correlated with cilia loss [ 3 , 7 ]. Nevertheless, in human thyroid tissue, the disappearance of cilia or their shortening has been associated with hyperactivity of the follicles [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is somewhat astonishing that especially KTC-1 cells, which are representatives of human thyroid carcinoma cells, exhibit cilia and maintain mTaar1-eGFP expression at them because in mice, papillary and follicular carcinoma are both correlated with cilia loss [ 3 , 7 ]. Nevertheless, in human thyroid tissue, the disappearance of cilia or their shortening has been associated with hyperactivity of the follicles [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of cilia or changes in their frequency are indicative of thyroid diseases, ranging from dysfunctional thyroid states to neoplastic pathologies [ 2 , 7 ]. While such correlations of thyroid pathologies with altered cilia length and numbers are important as diagnostic criteria in thyroid disease, little is known about the molecular mechanisms that connect cilia with altered thyroid states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of PC on ATC cells was associated with TC tumorigenesis and progression (10). However, a study from Junguee Lee et al demonstrated that loss of PC in PTCs results in increased apoptosis, and it is associated with reduced tumor aggressiveness (4). In this context, the loss of PC appears to select TC cells with more malignant features.…”
Section: Abnormal Length and Frequency Of Pc In Tcmentioning
confidence: 99%
“…PC is well preserved in PTC and FTC, and their frequency and length appear similar to those of normal thyroid follicles. Interestingly, defects in PC genesis have been observed in ATC ( 4 ). Additionally, oncogenic alterations, coupled to specific intracellular downstream signaling pathways, lead to the development of different subtypes of TC.…”
Section: Introductionmentioning
confidence: 99%